El juego como instancia recreativa en el aprendizaje de los niños de educación inicial de la escuela fiscomisional Pedemonte Mosquera del cantón Yacuambi de la provincia de Zamora Chinchipe - Gonzalez Quezada, Carmen Luisa (2014)
This research is a study about THE GAME AS A LEISURE INSTANCE IN CHILDREN’S LEARNING OF EARLY CHILDHOOD EDUCATION OF “PEDEMONTE MOSQUERA” FISCAL MISSIONARY SCHOOL FROM YACUAMBI CANTON, ZAMORA CHINCHIPE PROVINCE. The General Objective was to determine the incidence of game as a recreational resource in the children’s learning process. The used methods in this researching process were the Inductive-Deductive, Analytic-Synthetic and Descriptive methods. The used technique and instrument was the survey which was applied to four teachers and thirty five children’s parents. After analyzing the results of the survey applied to teachers and director, mainly it was concluded that 100% of this segment of the population consider that including games is a good teaching strategy for class development; Despite of this, only 75% of the surveyed teachers say to use game incisively in their daily practice in order to strengthen the children’s institutional adaptation, at the same time that game provides spaces for their recreation and promotion of specific learning. In relation to that, there is an average of 50% of teachers that prefer traditional games, and another similar percentage that prefer construction games Regarding the results of the children’s parent’s survey, this time it is concluded that a significant percentage of 71% of Parents are convinced that children learn better by participating in recreational activities at the same time they stimulate interaction positive attitudes; so 69% of them confirm the idea that they should not deprive the game but to dose, especially for the infants take other kinds of activities in which they must also act responsibly such as meeting their school requirements.